Fermentation studies on chayote (Sechuim edule Sw.) - Ramos, Ma. Lydia J.
The proper salt concentration and temperature condition for fermenting chayote (Sechium edule sw.) were studied. Salt concentrations of 20 deg, 30 deg, and 40 deg were tested. Two conditioned temperature, 67+-3 F. The sequence of the fermentation was determined. Room temperature with an initial brine of 20 deg salometer was found to be the best salt-temperature condition. The sequence observed was the following: Leuconostoc mesenteroides, Pediococcus cereviseae and Lactobacillus brevis.